Persistent Nociception Facilitates the Extinction of Morphine-Induced Conditioned Place Preference. (September 2019) - You, Zerong; Ding, Weihua; Doheny, Jason T.; Yang, Jinsheng; Yang, Liuyue; Lim, Grewo; Miao, Jiamin; Chen, Lucy; Shen, Shiqian; Mao, Jianren
Abstract : BACKGROUND: As opioid abuse and addiction have developed into a major national health crisis, prescription of opioids for pain management has become more controversial. However, opioids do help some patients by providing pain relief and improving the quality of life. To better understand the addictive properties of opioids under chronic pain conditions, we used a conditioned place preference (CPP) paradigm to examine the rewarding properties of morphine in rats with persistent nociception. METHODS: Spared nerve injury (SNI) model was used to induce persistent nociception in rats. Nociceptive behavior was assessed by von Frey test. CPP test was used to examine the rewarding properties of morphine. RESULTS: Our findings are as follows: (1) SNI rats did not show a difference compared with sham rats in magnitude of morphine-induced CPP 1 day after last morphine injection (2-way analysis of variance; for SNI versus sham, F [1, 42] = 0.014, P = .91; and 95% confidence intervals for difference of means, −5.9 [−58 to 46], 0.76 [−51 to 53], and 0.90 [−51 to 53] for 2.5, 5, and 10 mg/kg, respectively); (2) increasing morphine dosage (2.5, 5, and 10 mg/kg) did not further increase the magnitude of CPP in both sham and SNI rats (for dosage: F [2, 42] = 0.94, P = .40); and (3) morphine-induced CPP persisted in sham rats but extinguished in SNI rats when tested at 8 days after last morphine injection (for sham versus SNI: Bonferroni correction, P < .006 for both 5 and 10 mg/kg doses; and 95% confidence intervals for difference of means, 80.3 [19.7–141] and 87.0 [26.3–148] for 5 and 10 mg/kg, respectively). CONCLUSIONS: Our data provide new evidence supporting the notion that the brain's reward circuitry changes in the context of persistent pain. This observational study suggests that future investigation into the neurobiology of opioid reward requires consideration of the circumstances in which opioid analgesics are administered.